Scalp and Forehead Injury: Management of Acute and Secondary Defects - Namin, Arya W.; Tassone, Patrick T.; Galloway, Tabitha L.I.; Renner, Gregory J.; Chang, C.W. David (Facial Plastic Surgery, 2021)
The primary challenges in scalp reconstruction are the relative inelasticity of native scalp tissue and the convex shape of the calvarium. All rungs of the reconstructive ladder can be applied to scalp reconstruction, albeit in a nuanced fashion due to the unique anatomy and vascular supply to the scalp. Important defect variables to incorporate into the reconstructive decision include site, potential hairline distortion, size, depth, concomitant infection, prior radiation therapy, planned adjuvant therapy, medical comorbidities, patient desires, and potential calvarium and dura defects.
Keywords: scalp; forehead; reconstruction; trauma